(3bUjOI GddZI GdaGQSjI (B((3aj GdcjejGA(B)s - (3eYR GdTQjYI eDjO GdOjf CHi ESeGYjd GdMSjf GdMSjf Hf Ydj GdWZQGFis; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3eWdYgG HYO GdHSedI(B: (3LGQ YfUQ gSJ CfOQ jcTLQ Gfcg HSjGQGSJ OQhi ERKeQ s
(3BNQgG (B:s
(3BNQGdTQM(B: (3gcPG cGf ai GdefJSN hdfG ai cKjQ eeG PcQ ai GdTQM fXQ dCfg bO Zad Yf GdJQcjH GdKGfi GdNGdO s
(3Vef eLehY , JQJjHgG (B: (3ef U (B8 - (3U(B9s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B89 s
Keywords: (3GdcjejGA h GdWHjYjGJs